Miskonsepsi Materi Fisika Gaya Sebagai Penyebab Kurangnya Kemampuan Berpikir Kritis dan Tingkat Literasi Sains - Azizah, Nur; Nur Avifah, Avrillian; David Hidayat , Osey; Kurniawati , Wahyu (Journal Innovation In Education, 2023)
Scientific literacy is a 21st century skill that every student must have. However, in fact, in the learning process, misconceptions occur which make it difficult for students to think critically in studying inappropriate material. The research method applies qualitative research. The instruments and data collection techniques used were literature studies. The data analysis applied is descriptive data analysis. The problems that usually occur are in the realm of analysis in science learning, one of which is style material. In this material, misconceptions often occur due to the many types of forces being studied. Apart from that, there are also misconceptions about the principles and applications so that students are confused when learning them. This is a problem for students' critical thinking skills which has an impact on student literacy nationally.